Pengaruh Sarana Prasarana dan Kualitas Pelayanan Terhadap Minat Kunjungan Wisatawan Alas Kedaton Desa Kukuh Kecamaran Marga Tabanan - Ayudila Larasati; I Nyoman Sujana (Jurnal Pendidikan Ekonomi Undiksha, 2026)
This study aims to determine the effect of infrastructure and service quality on tourists’ visiting interest at the Alas Kedaton Tourist Attraction, located in Kukuh Village, Marga District, Tabanan. This research employs a causal quantitative design. The total population in this study is unknown; therefore, the data are treated as an infinite population. The sampling technique used is purposive sampling, with a total of 110 respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The hypothesis was tested using the t-test and F-test, with SPSS version 25 software. The results of the study indicate that: (1) partially, infrastructure has a positive and significant effect on tourists’ visiting interest; (2) partially, service quality also has a positive and significant effect on tourists’ visiting interest; and (3) simultaneously, both variables have a positive and significant effect on tourists’ visiting interest at the Alas Kedaton Tourist Attraction. Based on these findings, it is recommended that the management improve supporting facilities and service quality to attract more tourists to visit Alas Kedaton,